2016
DOI: 10.20344/amp.7306
|View full text |Cite|
|
Sign up to set email alerts
|

Tratamento de Tumores Neuroendócrinos Gastroenteropancreáticos com 177Lu-DOTA-TATE: Experiência do Instituto Português de Oncologia do Porto

Abstract: Introduction: The purpose of this article is to report the experience of Instituto Português de Oncologia do Porto in the treatment of gastroenteropancreatic neuroendocrin tumors with 177Lu-DOTA-TATE, regarding the safety and efficacy of this treatment modality.Material and Methods: A retrospective analysis of clinical reports of patients with gastrentheropancreatic neuroendocrine tumors undergoing treatment with 177Lu-DOTA-TATE between April 2011 and November 2013 was performed.Results: Thirty six cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…2 The median disease control rate (DCR) was 83% (range, 50-94%) and the median objective response rate (ORR) was 58% (range, 13-73%). 37,[56][57][58][59][60][61][62][63] The median PFS ranged from 25 to 34 months with a median OS of 42 to 71 months. 30,37,57,60,61,64 A retrospective study of 74 patients with GEP NET showed that panNET patients had a higher ORR (modified SWOG criteria), 73% vs 39% (p=0.005).…”
Section: Lu-dotatatementioning
confidence: 99%
“…2 The median disease control rate (DCR) was 83% (range, 50-94%) and the median objective response rate (ORR) was 58% (range, 13-73%). 37,[56][57][58][59][60][61][62][63] The median PFS ranged from 25 to 34 months with a median OS of 42 to 71 months. 30,37,57,60,61,64 A retrospective study of 74 patients with GEP NET showed that panNET patients had a higher ORR (modified SWOG criteria), 73% vs 39% (p=0.005).…”
Section: Lu-dotatatementioning
confidence: 99%